Development of two highly sensitive forensic sex determination assays based on human DYZ1 and Alu repetitive DNA elements. Issue 21 (18th October 2014) - Fazi, Amanda; Gobeski, Brianne; Foran, David; McCord, Bruce
<x xml:space="preserve">Abstract</x> Sex determination is a critical component of forensic identification, the standard genetic method for which is detection of the single copy amelogenin gene that has differing homologues on the X and Y chromosomes. However, this assay may not be sensitive enough when DNA samples are minute or highly compromised, thus other strategies for sex determination are needed. In the current research, two ultrasensitive sexing assays, based on real‐time PCR and pyrosequencing, were developed targeting the highly repetitive elements DYZ1 on the Y chromosome and Alu on the autosomes. The DYZ1/Alu strategy was compared to amelogenin for overall sensitivity based on high molecular weight and degraded DNA, followed by assaying the sex of 34 touch DNA samples and DNA from 30 hair shafts. The real‐time DYZ1/Alu assay proved to be approximately 1500 times more sensitive than its amelogenin counterpart based on high molecular weight DNA, and even more sensitive when sexing degraded DNA. The pyrosequencing DYZ1/Alu assay correctly sexed 26 of the touch DNAs, compared to six using amelogenin. Hair shaft DNAs showed equally improved sexing results using the DYZ1/Alu assays. Overall, both DYZ1/Alu assays were far more sensitive and accurate than was the amelogenin assay, and thus show great utility for sexing poor quality and low quantity DNA evidence.